Nanocomposites with superparamagnetic behavior based on a vegetable oil and magnetite nanoparticles - Meiorin, Cintia (2014)
The direct reaction of unmodified tung oil and styrene initiated by boron trifluoride diethyl etherate allowed obtaining thermoset polymers with valuable properties like shape memory behavior. On the other hand, the addition of magnetite nanoparticles (MNPs) to the tung oil/styrene copolymer was considered, in order to improve/modify its properties. MNPs were synthesized by the method of alkaline coprecipitation, followed by coating with oleic acid in order to hydrophobize their surfaces and make them more compatible with the polymeric matrix. Thus, superparamagnetic polymer nanocomposites were prepared from the inclusion of the MNPs to the cationically copolymerized tung oil (TO) and styrene (St) networks. The morphology, dynamic–mechanical and mechanical properties of the copolymers as well as magnetic behavior were significantly affected by the variation of the concentration of the MNPs.